2021
DOI: 10.1016/j.jbc.2021.100299
|View full text |Cite
|
Sign up to set email alerts
|

Human Gb3/CD77 synthase produces P1 glycotope-capped N-glycans, which mediate Shiga toxin 1 but not Shiga toxin 2 cell entry

Abstract: The human Gb3/CD77 synthase, encoded by the A4GALT gene, is an unusually promiscuous glycosyltransferase. It synthesizes the Galα1→4Gal linkage on two different glycosphingolipids (GSLs), producing globotriaosylceramide (Gb3, CD77, P k ) and the P1 antigen. Gb3 is the major receptor for Shiga toxins (Stxs) produced by enterohemorrhagic Escherichia coli . A single amino acid substitution (p.Q211E) ramps up the enzyme’s promiscuity, rendering i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…Stx1 interacts exclusively with the carbohydrate moiety of Gb3, while Stx2 needs additional interactions with the full glycolipid (Gallegos et al, 2012). This necessity has also been recently demonstrated in studies using the P1 glycotope, which was N-linked to the synthetic membrane protein Saposin D. This synthetic receptor mediated Stx1 entry into cells, but not the uptake of Stx2 (Szymczak-Kulus et al, 2021). Furthermore, Stx1 and Stx2 prefer to bind to Gb3 containing an α-hydroxyl fatty acyl chain, but not to a Gb3 analog without the hydroxyl group (Binnington et al, 2002).…”
Section: Structural Analysis Of Shiga Toxin -An Ab 5 Bacterial Holotoxinmentioning
confidence: 81%
See 1 more Smart Citation
“…Stx1 interacts exclusively with the carbohydrate moiety of Gb3, while Stx2 needs additional interactions with the full glycolipid (Gallegos et al, 2012). This necessity has also been recently demonstrated in studies using the P1 glycotope, which was N-linked to the synthetic membrane protein Saposin D. This synthetic receptor mediated Stx1 entry into cells, but not the uptake of Stx2 (Szymczak-Kulus et al, 2021). Furthermore, Stx1 and Stx2 prefer to bind to Gb3 containing an α-hydroxyl fatty acyl chain, but not to a Gb3 analog without the hydroxyl group (Binnington et al, 2002).…”
Section: Structural Analysis Of Shiga Toxin -An Ab 5 Bacterial Holotoxinmentioning
confidence: 81%
“…In humans and other mammals, the αGal14Gal epitope was considered to be present only on glycolipids (Gb3 and P1 antigen), but it was recently demonstrated that the Gb3 synthase can also produce αGal14Gal-capped N-glycans in transfected CHO cells ( Szymczak-Kulus et al, 2021 ). This epitope is widely present on N-glycoproteins in birds with substantial similarity between pigeon α4GalT and human Gb3 synthase (72.5%) ( Suzuki et al, 2004 ).…”
Section: Background and Importance Of The Glycosphingolipid Gb3mentioning
confidence: 99%
“…Recent reports proposed that human Gb3/CD77 synthase can also attach Gal residues to glycoprotein acceptors, contrary to the long-standing belief that it can only use glycosphingolipids [ 14 , 35 ]. If the human and avian enzymes indeed synthesize similar products, it would rule out the possibility that birds are refractory to Shiga toxins due to a lack of functional receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of Stx cytotoxicity is quite well understood, but some aspects of receptor recognition remain unclear. There is a general agreement that the main receptor for Stx is Gb3, while the hypothesis that glycoproteins containing Galα1→4Gal could be alternative receptors was long abandoned but recently revisited [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theu nexpectedly high reactivity of the bacterial 2,6sialyltransferase towards the folded EPO A glycoprotein provides rapid access to the sialylated glycoform EPO S in as ingle step.T his straight-forward transformation bypasses the need to synthesize the three sialoglycopeptide building blocks 33-35 and carry them through at ime-consuming process involving multiple ligations,p eptide modifications and protein refolding. Theo bserved high efficiency of the late-stage enzymatic sialylation of EPO A is very encouraging.M ost likely other homogeneous glycoproteins can also be modified analogously,h owever, the feasibility and efficiency of this approach need to be evaluated on ac ase-to-case basis.T he efficient enzymatic a-1,4-galactosylation [46] of afolded N-glycoprotein was recently shown using asynthetic glycoform of Saposin D containing ab iantennary N-glycan. [16] From our experiences well-behaved proteins are preferred substrates since they readily withstand the conditions of the enzymatic reactions and the following purifications leading to good overall yields.…”
Section: Methodsmentioning
confidence: 99%